Characteristics of Von Bertalanfy Growth, Allometric, Condition Index And Mortality of Periophthalmus barbarus in Mangrove and Probiotics Conservation Area (KKMB), Tarakan, North Kalimantan - Agus Indarjo; Gazali Salim; Mufrida Zein; Susiyanti Susiyanti; Permana Ari Soejarwo; Christine Dyta Nugraeni; Stephanie Bija; Yen Thi Hong Pham (Marine Science Department Diponegoro University, 2020)
The Mudskipper (P. barbarus) lives in intertidal mud flats and it becomes an indicator of water quality. The transformation of construction and water pollution in this area is important to investigate due to interaction of fishery industry, home residence, and market area surrounding areas. The aim of this research was to analyze the characteristic of Von Bertalanffy growth, allometric, condition index, and mortality of the P. barbarus in KKMB, Tarakan city. The research was designed by using descriptive quantitative method. The sampling process used purposive sampling. The sampling was conducted for 12 times plot.transect-1 in the extension area of KKMB, Tarakan city with a total area is 12 Ha, plot.transect-1area is 10x10 m2, and distance between each transect is 10 m2. Sampling was carried out in survey area and laboratory to identify the gender and calculate total length and weight. The result showed the growth of male mudskipper (L∞ = 26.545 cm) and female (L∞ = 17.594 cm). Their size and the total population was decreased. The characteristic of male mudskipper growth was positive allometric, then female was negative allometric. The natural mortality and the catch of male mudskipper were higher than female.